DNA methylation in invertebrate genomes and cell lineage plasticity - Laurel S. Hiebert; Soojin V. Yi (Proceedings of the National Academy of Sciences, 2026)
The extent of DNA methylation varies widely across animal genomes, from almost undetectable levels in some taxa to high, pervasive methylation in others. Although DNA methylation has been linked to gene regulation, genome defense, and cellular memory, the evolutionary forces shaping its diversity across taxa remain unresolved. Using phylogenetic comparative analysis of 175 invertebrate species spanning 14 phyla, we show that species with greater regenerative capacity exhibit higher genome-wide CpG methylation, independent of phylogenetic relatedness. This relationship suggests that higher genomic DNA methylation is associated with traits indicative of greater somatic lineage renewal and cell lineage plasticity. We propose that, under such conditions, variation in DNA methylation among dividing cells may influence how cell lineages persist, expand, or are replaced within tissues. Thus, we hypothesize that cross-species variation in DNA methylation may reflect differences in somatic lineage renewal and and opportunities for within-body selection.